Relasi Sosial Yahudi dan Islam - Hasbi Siddiq (TASAMUH: Jurnal Studi Islam, 2015)
Between the Christian, Jews, and Islam religion, which have the bigger follower than Judaism. The Judaism, in history like Buddda, is closed minded and ethnocentric. The geneology between Islam and Yahudi is rising in father of prophet, Abraham. Abraham from his wife, Siti Hajjar, bear Ismail and Ishaq. From the children bear many prophets to continue proceedings and unity of God. In Madina, when Muhammad built civilization and invited men to Islam, Judaism spoils between them, Muhammad and follower. The claim of Judaism is, they son of God and the ummah in the world. In the Judaism perspective, the prophet is only in Bani Israil. Muhammmad is not from them, they destroy the Mou. They try to take effect in follower Muhammad to question of existence of Muhmmad as Prophet